Analytical simulation of reinforced concrete beam with four openings using ansys software - Ngiam, Tee Hung (2014)
Construction of structural using beam with opening be an alternative way to solve the limited spaces available for installation of pipes or ducts The additional services pipes underneath the beam will cause reduction in dead space In term of cost saving, opening in beam for small buildings doesn't really affect much but it will give a huge impact for the high buildings However the opening in beams can make huge significant changes on the simple beam behavior to complex one. Beam with openings will not only affect the overall behavior of the beam, it will also eventually affect the serviceability and ultimate limit state of a building. There have been numerous of engineering software available on the market for analysis such as STAAD.Pro, LUSAS, and MATLAB but most of them are expensive and it is hard to obtain its license for small companies ANSYS with finite element modeling have been widely used to analyse for structural problem hence the study will be based ANSYS using Finite Element Method Numerical solutions to even complicated stress problems can be obtained by using ANSYS and Civi1FEM This study is going to be basic guidelines for civil engineer to analyse the beam openings by using ANSYS software. This study is conducted to analyse beam with four opening by, using simulation of various loadings using ANSYS software. The objective of this study is analysing the result based on its strength behavior, deflection, and stress and strain using simulation with various loading.